The role of accounting and cloud auditing standards in confirming data security and information (A field study from the point of view of external accounts in Syria) - حبيب, سمر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed to investigate the views of external accounts in Syria on the role of the benefits and risks of accounting and cloud auditing when alerting cloud solutions, and their opinions on the role of cloud audit standards (SAS70, SSAE16, ISO295TC) in confirming data and information security, in addition to investigating their opinions on the extent of availability Data security controls and information issued by international professional bodies and organizations in the rules and systems issued by the Syrian legislator, and the study relied on the design of a questionnaire that was distributed electronically on the study sample and several results were reached, which is the presence of statistically significant differences in the opinions of external accounts (study sample) On both the role of the benefits and risks of accounting and cloud audit when alerting cloud solutions,, the role of cloud audit standards in confirming data security and information, and the availability of data security controls and information in the rules and regulations issued by the Syrian legislator, and these differences came according to the scientific qualification, scientific specialization, and years of experience in the field of audit, Also, some recommendations were proposed, the most important of which is the necessity of achieving harmony between the benefits and risks of accounting and cloud auditing when adopting the solution And cloud, be careful in choosing cloud services providers, looking at data security and information as an administrative issue and not just a technical issue.